2015
DOI: 10.1016/j.ejar.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies on the effect of cadmium chloride, zinc acetate, their mixture and the mitigation with vitamin C supplementation on hatchability, size and quality of newly hatched larvae of common carp, Cyprinus carpio

Abstract: The present results show that the fertilization and hatching rates, as well as the development of the embryos of common carp are adversely affected by heavy metal pollution. The degree of this effect depends on the duration and the concentration of the heavy metal used. Malformation of the yolk sac and curvature in the abdominal region were also observed throughout this study. No statistical difference was recorded between the polluted group which was supplemented with vitamin C (300 mg/kg of dry feed), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Because most of the open water environment is contaminated with mixtures of heavy metals (from anthropogenic and geogenic sources), it is important to evaluate the combined effects of those heavy metals on embryonic and larval development. The combined effect of Cu-Zn and Cd-Zn has been investigated in Rainbow trout Oncorhynchus mykiss [48] and common carp Cyprinus carpio [49] embryos respectively, revealing increased embryonic mortality and physical deformities (e.g. vertebral column deformities).…”
Section: Heavy Metals Effects On Embryonic and Larval Development Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Because most of the open water environment is contaminated with mixtures of heavy metals (from anthropogenic and geogenic sources), it is important to evaluate the combined effects of those heavy metals on embryonic and larval development. The combined effect of Cu-Zn and Cd-Zn has been investigated in Rainbow trout Oncorhynchus mykiss [48] and common carp Cyprinus carpio [49] embryos respectively, revealing increased embryonic mortality and physical deformities (e.g. vertebral column deformities).…”
Section: Heavy Metals Effects On Embryonic and Larval Development Of ...mentioning
confidence: 99%
“…Supplementation of vitamin C with the dry feed to the embryo and larvae of common carp ( Cyprinus carpio ) exposed to mixture of Zn and Cd increased the ontogenic development and quality and quantity of the larvae through the improvement of immune system [49] . It has been reported that Cd exposure under conditions of high alkalinity can significantly increase the hatching, survival rate and growth of larvae of Silver catfish Rhamdia quelen [50] .…”
Section: Heavy Metals Effects On Embryonic and Larval Development Of ...mentioning
confidence: 99%
“…It may reach 2 mg/L in contaminated water [ 3 ]. Cd accumulates rapidly in the organs and tissues of rainbow trout Onchorhynshus mykiss [ 4 ] and tilapia Oreochromis niloticus [ 5 ] and may diminish growth; affect behavior, plasma ion balance, and respiration of O. mykiss [ 6 ], O. niloticus [ 7 ], and carp Cyprinus carpio [ 8 ]; suppress hormone activity of Prussian carp Carassius auratus gibelio [ 9 ] and Neotropical fish Rhamdia quelen [ 10 ]; inhibit reproduction of red tilapia Oreochromis sp [ 11 ] and neotropical fish Prochilodus magdalenae [ 12 ]; lower hematological, biochemical parameters; and disrupt enzyme function of O. niloticus [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…It may reach 2 mg/L in contaminated water (Cao et al, 2012). Cd accumulates rapidly in the organs and tissues of rainbow trout Onchorhynshus mykiss (Heydarnejad et al, 2013) and tilapia Oreochromis niloticus (Soegianto et al, 2022a) and may diminish growth, affect behavior, plasma ion balance and respiration of O. mykiss (McGeer et al, 2000), O. niloticus (Atli & Canli, 2013), and carp Cyprinus carpio (El-Greisy & El-Gamal, 2015), suppress hormone activity of Prussian carp Carassius auratus gibelio (Szczerbik et al, 2006) and Neotropical sh Rhamdia quelen (Vicentini et al, 2022), inhibit reproduction of red tilapia Oreochromis sp (El-Ebiary et al, 2013) and Neotropical sh Prochilodus magdalenae (Sierra-Marquez et al, 2019), lower hematological, biochemical parameters, and disrupt enzyme function of O. niloticus (Al-Asgah et al, 2015;Adam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%